Analisis Dan Perbandingan Kurikulum Indonesia Abad Ke – 20 - Fuad, Fitri Qurrota A’yunin; Lailiyah, Shefy Badrul; Wahyono, Argo Adi; Ahid, Nur (JoEMS (Journal of Education and Management Studies), 2023)
The purpose of this study is to understand the development of the curriculum in Indonesia from year to year (2004 Curriculum - Merdeka Curriculum), then to know the advantages of the curriculum in Indonesia from year to year (2004 Curriculum - Merdeka Curriculum) and to know the shortcomings of the curriculum in Indonesia from year to year (2004 Curriculum - Merdeka Curriculum). The type of research used in this research is library research which is based on literature review/content analysis and refers to documents or records as its data source with a qualitative descriptive design. The results of this study can be seen in the fact that curriculum changes are a form of influence from changes in the law on the national education system. The curriculum as a set of educational plans needs to be developed dynamically in accordance with the demands and changes that occur in society. The entire national curriculum is designed based on the same foundation, namely Pancasila and the 1945 Constitution, the difference is in the main emphasis of educational goals and approaches in realising them. In the history of curriculum development in Indonesia in the 20s, four times were recorded, namely since 2004, the national curriculum changed from 2004, 2006, 2013 and the independent curriculum as the current policy. Each curriculum has advantages and disadvantages. And this curriculum can change at any time according to the needs of Indonesian education.